A Bibliometric Analysis of Social Media Utilization in Election Campaign Strategies; Trends, Dynamics, and Impacts on Scopus Data from 2019 to 2024 - Nursaripati Risca; Alamsyah; Adi Abdillah; Nida'ul Hafiyah; Alem Febri Sonni; Elvira Naharni Sisca (Mediakita, 2025)
This study aims to analyze the literature on social media use in political campaigns using a bibliometric analysis approach, which enables the identification of trends, patterns, and collaboration networks in related research. Using data from 166 publications indexed in Scopus, this study analyzes the development of research on social media and politics. The bibliometric analysis method employed in this research includes data collection through the Scopus database with specific filters, data cleaning using the Open Refine application, and visualization of the research network using VOSviewer. The analysis results show that the research trends significantly increase, focusing mainly on social media, political communication, and elections. Countries such as Spain and Germany dominate publications on these topics. Furthermore, leading institutions such as Eötvös Loránd University and LMU Munich are essential in developing knowledge in this field. The research concludes that while social media opens great opportunities for political participation, these platforms also bring serious challenges, especially regarding disinformation and polarization. It also recommends the need for a multidisciplinary approach to understanding the impact of social media in political campaigns, as well as the importance of international collaboration and more inclusive research on gender issues and digital algorithms.